THE ANALYSIS OF EFFECT SIZE AND THE EFFECT OF TEACHING MATERIALS BASED ON PROBLEM BASED LEARNING (PBL) ON STUDENTS’ COMPETENCE - Syamina Syamina; Asrizal Asrizal; Festiyed Festiyed (JURNAL TARBIYAH, 2021)
Science in the 21st century continues to develop. With these developments, Indonesia must prepare young people who are ready for change and able to face the challenges that exist in the 21st century. The 21st century has more complex challenges. Various efforts have been made by the government to meet the demands of the 21st century, including reforming educational standards. The 2013 curriculum requires students to be active in the learning process. Learning methods and models that are expected to be able to develop students' abilities, and in accordance with the implementation of the 2013 curriculum, are problem-based learning. Therefore, researchers are interested in finding the effect of PBL-based teaching on student learning outcomes through meta-analysis with effect size. Based on the analysis conducted on 20 journals related to PBL-based teaching materials, there are three conclusions in this study. First, PBL-based teaching materials are effectively used at the junior and senior high school levels with a high effect size category. Second, PBL-based teaching materials have the highest category of effectiveness in improving science process skills. Third, based on the teaching materials used, teaching materials in the form of electronic media (IT) based on PBL are effective in improving student learning outcomes.